2013
DOI: 10.1139/cjm-2012-0673
|View full text |Cite
|
Sign up to set email alerts
|

Role of a TehA homolog inVibrio choleraeC6706 antibiotic resistance and intestinal colonization

Abstract: Vibrio cholerae is the causative agent of the devastating diarrheal disease cholera. A number of regulatory pathways are involved in V. cholerae pathogenesis and antibiotic resistance. For example, there are over 40 LysR-family proteins in the V. cholerae genome, but most of their functions are unknown. In this study, we examine the role of VC2323 (TehAVc) and its divergently transcribed LysR-family regulator VC2324 (TehRVc) in V. cholerae pathogenesis. We found that in V. cholerae C6706, the expression of teh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…One of the chromosomal Te R determinants is the operon teh AB, originally described in E. coli . Homologues and orthologues of the teh A gene have been identified in other bacterial species, such as Vibrio cholerae, Klebsiella pneumoniae, Salmonella enterica and Corynebacterium glutamicum ( Chasteen et al 2009 , Pei et al 2013) . Recent studies have revealed that this determinant did not confer the Te R mechanism of V. cholerae C6706, but was found involved in antibiotic resistance and intestinal colonisation ( Pei et al 2013) .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One of the chromosomal Te R determinants is the operon teh AB, originally described in E. coli . Homologues and orthologues of the teh A gene have been identified in other bacterial species, such as Vibrio cholerae, Klebsiella pneumoniae, Salmonella enterica and Corynebacterium glutamicum ( Chasteen et al 2009 , Pei et al 2013) . Recent studies have revealed that this determinant did not confer the Te R mechanism of V. cholerae C6706, but was found involved in antibiotic resistance and intestinal colonisation ( Pei et al 2013) .…”
Section: Discussionmentioning
confidence: 99%
“…A recent report indicated that TehA protein participates in V. cholerae antimicrobial resistance ( Pei et al 2013 ). In contrast, the findings presented here indicated that the TehA homologue is not involved in the susceptibility of C. diphtheriae to the antimicrobial agents tested.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations